Organizational Culture as a Catalyst for Literacy Development in Islamic Boarding School - Humaidi, Rif'an (JURNAL AL-TANZIM, 2024)
Organizational culture in Islamic boarding schools plays a crucial role in improving students' literacy. Identifying the most influential cultural elements can help develop strategies to strengthen literacy skills among students. This study aims to analyze the role of organizational culture in promoting students' literacy in Islamic boarding schools. The research method used is qualitative, with a case study approach involving interviews, observations, and documentation. Data analysis using the Miles and Huberman model includes data reduction, systematic data presentation, and conclusion. The results of this study indicate that a conducive learning environment in Islamic boarding schools, strengthening sustainable literacy programs, effective collaboration with external partners, and developing values and norms by Islamic boarding school principles significantly contribute to improving students' literacy. These findings emphasize the importance of a holistic approach involving various aspects of organizational culture to achieve better student literacy outcomes. This study provides implications for Islamic boarding school management's importance in strengthening cultural elements that support literacy. In addition to providing new insights, this study contributes significantly to educational policies in Islamic boarding schools.